2009
DOI: 10.1037/a0014891
|View full text |Cite
|
Sign up to set email alerts
|

The value of value congruence.

Abstract: Research on value congruence has attempted to explain why value congruence leads to positive outcomes, but few of these explanations have been tested empirically. In this article, the authors develop and test a theoretical model that integrates 4 key explanations of value congruence effects, which are framed in terms of communication, predictability, interpersonal attraction, and trust. These constructs are used to explain the process by which value congruence relates to job satisfaction, organizational identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
1,355
3
26

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,136 publications
(1,422 citation statements)
references
References 153 publications
38
1,355
3
26
Order By: Relevance
“…Section 4 describes our results and Section 5 concludes, while some details of the ethical dilemmas are provided in the Section 6, the Appendix. 5 We will have more to say on this below, but the degree to which an employee's personal ethical opinions overlap with the norms actually held by his peers or with the ethical norms held by the corporate leadership can be thought of as a measure of 'fit' (see Edwards andCable 2009, Ambrose et al 2008;Herrbach and Mignonac 2007;Schminke et al 2005, Valentine et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Section 4 describes our results and Section 5 concludes, while some details of the ethical dilemmas are provided in the Section 6, the Appendix. 5 We will have more to say on this below, but the degree to which an employee's personal ethical opinions overlap with the norms actually held by his peers or with the ethical norms held by the corporate leadership can be thought of as a measure of 'fit' (see Edwards andCable 2009, Ambrose et al 2008;Herrbach and Mignonac 2007;Schminke et al 2005, Valentine et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we utilized the block variable approach recommended by Edwards and Cable (2009). In this context, the relationship between the personality polynomial terms and positive emotional displays (i.e., the After estimating the path between the personality polynomial terms and positive emotional displays, we then estimated the relationship between positive emotional displays and the negotiation outcomes after controlling for the effects of personality similarity (i.e., the "b" path in the mediation models).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we utilized the block variable approach recommended by Edwards and Cable (2009). In this context, the relationship between the personality polynomial terms and positive emotional displays (i.e., the "a" path in a mediation model), is estimated by creating a "block variable" for each dyad by multiplying the estimated polynomial regression coefficients from equation 1 pertaining to personality similarity (i.e., b1 through b5) with each dyad's raw data to obtain a series of weighted linear composite values.…”
Section: Discussionmentioning
confidence: 99%
“…Third, under the condition of incomplete consistency, the dependent variable values and changes with the independent variables are proved. Edwards & Cable (2009) [5] , Edwards & Parry(1993) [6] showed that there is very little perfect consistency effect. Under the premise of not completely matching, polynomial regression equation and response surface analysis have a great practical value to potential information.…”
Section: Theoretical Contribution Of the Research Resultsmentioning
confidence: 99%